An Asymmetric Analysis of Renewable Energy in Mitigating Carbon Emissions in Pakistan - Asghar, Nabila; Amjad, Muhammad Asif; Rehman, Hafeez ur (iRASD Journal of Economics, 2023)
To achieve sustainable growth, energy is incumbent because all modern production is based on it. Unfortunately, about 80% of the global population uses polluted energy, adversely damaging the environment. The present study asses the asymmetric role of renewable energy in the mitigation of CO2 emissions in Pakistan. The Non-linear ARDL econometric approach is used to estimate the empirical results of the time series data from 1980 to 2020. The study found that positive change in renewable energy adversely declines CO2 emissions while negative change increases CO2 emissions. Additionally, the HDI and trade openness lessens CO2 emissions, while urbanization increases CO2 emissions. The study recommends that Pakistan should promote eco-friendly consumption patterns. Pakistan should focus on promoting renewable energy resources, which will help combat the upsurge in industrial and housing carbon dioxide emissions.